2021
DOI: 10.3389/pore.2021.1609867
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Stem Cell Transplantation for Relapsed and Refractory Hodgkin Lymphoma: Real World Experience of a Single Center

Abstract: Introduction: Refractory and relapsed Hodgkin lymphoma (R/R HL) is associated with poor prognosis, and allogeneic stem cell transplantation (allo-SCT) remains the only potentially curative approach.Aim: The aim of the study was to evaluate the feasibility of allotransplantation in R/R HL setting.Material: Overall, 24 patients (17 men and 7 women) at a median age of 27 years (range 18–44) underwent allo-SCT between 2002 and 2020.Results: Nineteen patients received prior autologous stem cell transplantation (ASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…hematologic malignancies, but it showed a high rate of NRM with a low probability of 3-year OS. A retrospective EBMT study on 168 HL patients compared the outcomes of RIC vs. MAC and it was found that the latter was associated with significantly higher NRM which translated into lower OS [5,8]. This is partially related to the idea of overcoming chemoresistance by increasing the total systemic dose to the highest possible amount while avoiding significant damage to organs other than the marrow.…”
Section: Discussionmentioning
confidence: 99%
“…hematologic malignancies, but it showed a high rate of NRM with a low probability of 3-year OS. A retrospective EBMT study on 168 HL patients compared the outcomes of RIC vs. MAC and it was found that the latter was associated with significantly higher NRM which translated into lower OS [5,8]. This is partially related to the idea of overcoming chemoresistance by increasing the total systemic dose to the highest possible amount while avoiding significant damage to organs other than the marrow.…”
Section: Discussionmentioning
confidence: 99%